Report of Annual review of “Partnerships for Scaling Climate Smart Agriculture Phase 2 (P4S II)’’ - Adeyemi, Chabi; Bayala, Jules; Dembélé, Catherine (World Agroforestry Centre, 2020)
P4S II resulted from the merging the actions of BRAS-PAR and P4S I with the intention to use tools and evidence/lessons learned from the Climate-Smart Villages and other development activities, with existing and new partners through direct scientific support to decision makers (e.g., governments, civil society, and researchers) and capacity building to help bring CSA to scale. The scientific activities will be combined with dedicated communications activities such as photo essays, tweets, blog posts, etc. from field staff and partners to raise the visibility of the project and help show case of its successes in supporting countries and position of ICRAF, CIAT, and CCAFS as the go to research organization for the science of scaling up CSA. The key activity areas of P4S II will be around: supporting CSA investment and programming, De-risking agriculture, digital delivery and monitoring and community based scaling of CSA. The present meeting reviewed the achievements for year 2019 of P4S and planed the new activities around these areas for 2020.